Penulisan Arab dan Pengaruhnya terhadap Pemahaman Teks Arabic Writing and its Influence on text Comprehension - Hulwatunnisa, Hulwatunnisa; Zuliana, Erni; Anggraeni, Wulan; Nariyah, Aini; Isma, Vidya; Milah, Aang Saeful (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
Arabic has its origins in the history of writing. This study aims to gather sufficient information about the history of Arabic writing and the influence of writing on the understanding of the writing. This research method is a literature study that collects some previous research to discuss the history of Arabic writing and answer what influence writing has on the understanding of the writing. The results showed that there are many opinions about the origin of the birth of Arabic script. At the time of the Prophet of Allah, the development of writing began in the 2nd year, the Prophet taught writing for prisoners who wanted to be released without having to pay a ransom. Arab society already has its own writing. Although still simple with a classical kufic form that does not have vowel markers and consonant differentiators. And also still do not know sentence markers such as dots, commas, or decorations in writing. So the arrival of the Qur'an made the development of Arabic writing better. Arabic writing is not free from mistakes. Errors in writing greatly affect reading comprehension, because even a single letter can change the meaning of reading. The comprehension of Arabic writing depends on knowledge of Arabic vocabulary and grammar.